A note on the national contributions to the euro area M3 - Aaron Mehrotra (Bank of Finland, 2007)
We examine developments in national contributions to euro area M3 for a sample of nine euro area countries during 1999-2005.We investigate the co-movements of national contributions with euro area M3 and discuss possible reasons for divergencies in growth rates of national contributions.Finally, we evaluate the information content of national contributions to M3 using formal tests of causality between monetary aggregates, consumer prices and equity prices.
URN:NBN:fi:bof-20140807497
Keywords: E51; E31; 330; national contribution; M3; euro area